Physical Characteristics of Bee Pollen Trigona sp Fermented Using Lactobacillus plantarum - Dinda Novita Sari; Ulfah Anis; Syafnil Syafnil (AGRITROPICA : Journal of Agricultural Sciences, 2026)
Bee pollen from Trigona sp is a natural product rich in bioactive compounds. However, the bioavailability of these compounds is limited due to the presence of exine walls in bee pollen. Fermentation methods using lactic acid bacteria, especially Lactobacillus plantarum, have been reported to increase the bioavailability of bioactive compounds in bee pollen. However, the fermentation process can affect the physical characteristics of the product, including color, total soluble solids (TSS), and pH. This study aimed to determine the effect of fermentation time on the physical characteristics of Trigona sp bee pollen fermented using L. plantarum. The results showed that fermentation time significantly affected the b* value, chroma, total soluble solids, and pH. However, it did not significantly affect the L*, a*, and hue angle values. The b* and chroma values ​​decreased with longer fermentation time due to carotenoid degradation under acidic conditions. Total soluble solids decreased because L. plantarum consumed sugar to produce lactic acid, which also caused a gradual decrease in pH during the fermentation process. These findings indicate that fermentation time plays a significant role in determining the physical quality of Trigona sp. bee pollen.